Dampak Penerapan Digital Marketing dan Personal Selling Ritel Terhadap Keputusan Pelanggan di Toko Jesika Store - Dinda Puspitasari; Sintia Aulia Agustin; Haya Nur Safa’atin (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to understand how digital marketing and personal selling strategies influence consumer purchasing decisions at Jesika Store. Using a qualitative approach, this study collected data through in-depth interviews with several customers who had interacted with both marketing methods. The results showed that digital marketing plays an important role in increasing brand awareness and market reach, while personal selling focuses more on building personal relationships that strengthen consumer trust, which ultimately influences their purchasing decisions. Both strategies have a significant influence in determining consumer choices.